The Hudson collection - Green, Jocelyn (Green, Jocelyn. On Central Park, 2024)
"An ornithologist at Manhattan's American Museum of Natural History, Elsa Reisner is tasked with cataloging a country Gothic estate. Once there, she bonds with the house's other occupants, including an intriguing carpenter from the Metropolitan Museum of Art, and is swept up in a treasure hunt for a priceless heirloom"--